The Goodness-Of-Fit Of Dass-21models Among University Students - Talwar, Prashanth; Tan, Kock Wah; Kartini, Abd Ghani; Nur Fatihah, Mat Yusoff (MJPHM, 2016)
Depression, anxiety and stress are the most prevalent mental health problems among university students, which may adversely influence their psychological wellbeing. Considering these problems, the Depression, Anxiety and Stress Scale-21 (DASS-21) may hold more promise as a screening tool. The present study sought to assess competing models of the latent factor structure of the DASS-21 utilizing Confirmatory Factor Analysis, and also to examine the multi group invariance. An exploratory cross-sectional study was conducted among undergraduate students recruited from a public university in Sarawak, Malaysia. The self-report English language questionnaire was administered to 254 students. SPSS version 21 was used for data analysis. Overall, the DASS-21 exhibited adequate reliability, with the three-factor model showing good fit to the data from the current study. Gender invariance was also adequately demonstrated. However, high inter correlations indicated that depression, anxiety and stress may not be distinguishable constructs, as was originally perceived.